LIBERAL FEMINIST VALUES THROUGH MALEFICENT’S PERSONALITY TRAITS IN MALEFICENT: MISTRESS OF EVIL FILM - Vermita Yolanda; Suci Budiwaty (UG Journal, 2022)
The objectives of this research were to find liberal feminist values and to discover Maleficent's personality traits in the film Maleficent: Mistress of Evil. This research employed Tong's liberal feminist theory to find liberal feminist values and used McCrae & Costa's theory to discover Maleficent's personality traits. The data were analyzed using a qualitative method. The data were taken from the film Maleficent: Mistress of Evil. This research discovered that Maleficent, as the main character, demonstrated that women deserved to be acknowledged as rational women and deserve to get the same civic liberties, formal education, economic possibilities, and other privileges as men. The result of this research showed that from the big five personalities, Maleficent has four personalities, namely agreeableness, neuroticism openness to experience, and the last is extraversion.